TL 18111 - Rate of unsatisfactory syndesmotic reduction according to a postoperative tomographic study - Christovan Ribeiro, Evandro Junior; Damião Prata, Sérgio; Rizzo, Marco Antônio (Scientific Journal of the Foot & Ankle, 2019)
Objective: To analyze the rate of unsatisfactory reduction of syndesmosis injuries through a postoperative tomographic study. Methods: This is a prospective study conducted from March to December 2017. In total, 30 patients with syndesmosis injury were selected, and ankle tomography was performed during the first postoperative period. A form developed for the study was used to collect demographic data (sex and age in years) and postoperative data (operated side, Weber classification, computed tomography results and need for surgical reoperation). The images were evaluated using tomographic criteria. The intraoperative analysis was based on the results of radioscopy and direct visualization of syndesmosis. Results: Most of the patients were male (56.7%), and their ages ranged from 17 to 51 years. A total of 53.3% of the patients underwent treatment of the left side, 66.7% of patients were classified as type C, and 66.7% of patients did not undergo reoperation. The rate of unsatisfactory syndesmosis reduction was 25.9% based on analyses of the established variables. Although 74.1% of the criteria presented satisfactory outcomes, criterion B had a significant rate (37%) of unsatisfactory outcomes. Conclusion: Tomographic analysis showed a high percentage of unsatisfactory reductions of syndesmosis injuries. Accordingly, despite the use of correct fixation techniques and adequate intraoperative scopic monitoring, postoperative tomography identified cases of distal tibiofibular joint incongruence.